The measurement of capital : theory and practice - Patterson, K. D.; Schott, Kerry E. (London : Macmillan, 1979)
The Book is divided into two parts. Part I. Theory. Part II. Practice. Nine of the papers presented here originate from a conference on the measurement of capital held at the University of Southampton in the summer of 1976. Two further papers, which are germane to the conference theme were not available at the time, are also included. The aim of the organisers was to promote discussion between theorists, statisticians and applied economists. This aim seems particularly relevant in the case of capital measurement.
Original imprint covered by label, as above.
Majority of the papers originally presented at the conference.
Includes bibliographical references and index.
rpm 08/11/2017
Loans
Keywords: Capital